HUBUNGAN PANJANG BOBOT DAN FAKTOR KONDISI IKAN BELANAK (Mugil dussumieri) DI MUARA SUNGAI KUMBE KABUPATEN MERAUKE - Sunarni Sunarni (AGRICOLA, 2017)
The mullet (Mugil dussumeiri) is one of the fish species in the estuary of the Kumbe River. The fish is used as consumption fish directly and processed into salted fish. The airms of this research is estimated the pattern and condition factors of Mugil dussumeiri in the estuary River Kumbe, Merauke regency. Determination of sampling location using purposive sampling method. The study was conducted from February to July 2016. The result shows that the relation of long weight of male mules W = 0.0001L2,47 and female W = 0,0002L2,43. The growth patterns of male and female Mugil dussumeiri due to allometric positive. The mean condition factor value in male is 1.45 and female is 0.89.